Theuseof spiritual practices andritualsby athletes inpreparation forthe competition - Olena Gant; Ksenia Mlikova (Kharkiv State Academy of Physical Culture, 2019)
The use of spiritual practices andritualsby athletes inpreparation forthe competition. The purpose of the study is to study the features of preparation for competitions in Ukrainian and Latvian athletes. Material and research methods: analysis of scientific and methodological literature, questionnaires, Rokich's "Value Orientations" methodology. Results A theoretical analysis of the problem of psychological preparation for the competition among athletes. It is determined that in addition to classical psychological techniques, athletes use various rituals and practice ovens. The attitude to responsibility for the result in competitions in Latvian and Ukrainian athletes is analyzed. Conclusions: % of the examined athletes use various ritual actions and spiritual practices before the competition, and at the same time take full responsibility for the result in the competition. The use of rituals and spiritual practices by athletes depends both on the cultural characteristics of the athletes examined, on their personal orientations and value orientations, religion and the strength of the nervous system.